Ultrasonic assisted improved extraction and dyeing of mordanted silk fabric using neem bark as source of natural colourant. Issue 14 (18th July 2019) - Adeel, Shahid; Zia, Khalid Mahmood; Abdullah, Muhammad; Rehman, Fazal-ur-; Salman, Mahwish; Zuber, Mohammad
Abstract: Natural products with therapeutic nature are nowadays warmly welcomed in textiles. Current study is concerned with isolation of tannin from neem bark ( Azadirachta indica ) and its application onto silk fabric. For improvement in shades, chemical & bio-mordants have been employed at optimal dyeing conditions. It is found that methanolic extract of pH 5 obtained 8 g dye powder after US Treatment for 30 min has given high color strength if used to dye irradiated silk for 65 min at 75 °C. Bio-mordanting using herbal plants has improved the color characteristics as compared to chemical mordants used. ISO standards for color fastness reveal that herbal based bio-mordants have improved the rating from good to excellent as compared to chemical mordants used. It is concluded that US treatment has not only isolate the colorant for neem bark under mild condition but also given excellent characteristic using bio mordants onto silk fabrics. Abstract :